Climate Change Risk Analysis of Argentina’s Land Transport Network - Kesete, Yohannes Y.; Raffo, Veronica; Pant, Raghav; Koks, Elco E.; Paltan, Homero; Russell, Tom; Hall, Jim W. (World Bank, Washington, DC, 2021)
Argentina’s vast networks of national, provincial, and rural roads, spanning more than 240,000 kilometers, are critical for the country’s growth and development. However, climate change–induced hydrological extremes often disrupt road travel and raise logistics costs. The objective of this study is to quantify the impact of climate change induced flood risk on the transport network in Argentina. The study analyzes both current and future flooding scenarios, examines the resulting disruptions in the transport network, and estimates the direct and indirect macroeconomic losses. The study uses a system-of-systems approach, where network models are developed to suitably represent the transport system as nodes and links. For each node and link, the study analyzes criticality, vulnerability, and risk, and provides adaptation strategies. This paper is organized into four sections. Following the methodology and approach laid out in Section 2, the analysis and results are detailed in Section 3,Conclusions and policy recommendations are presented in Section 4.